VALIDATION OF THE SELF-COMPASSION SCALE IN A MALAYSIAN SAMPLE - Harris Shah Abd Hamid; Badar Salim Saleh; Feezyha Azmi; Hong Trang Doan; Lee Xue Jing; Lim Joo Yee; Nurul Saira Alina Che Sakari; Ooi Giap Sim; Yew Sheng Jie, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The Self-Compassion Scale (SCS) was developed to evaluate and capture how people act toward themselves in difficulties times. Although there were reports of its use in Malaysia, evidence of its validity is limited. A study was conducted to examine the factor structure and to externally validate the original English version in a Malaysian sample of adults (n=222; 73 males, 149 females). Results from the online survey show that a six-factor structure provides a better fit to the data than a two-factor structure. Composite reliability and average variance extracted showed limited reliability and construct validity evidence. Construct validity was also tested with measures of anxiety (State-Trait Anxiety Inventory), stress (Perceived Stress Scale), social support (Multidimensional Scale of Perceived Social Support), and life satisfaction (Satisfaction with Life Scale). The SCS is significantly correlated in the expected direction with mental health outcomes. Additionally, internal consistency and test-retest reliability indices are acceptable. Thus, overall, SCS may be considered as having good validity and reliability with the tested sample. With validation of the English version of SCS, translation of SCS into local languages would be the next step in extending the use of SCS in the wider Malaysian population.